2011
DOI: 10.2478/v10078-011-0072-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Physical Effects of Different Milk Protein Supplements in Elite Soccer Players

Abstract: Brazilian soccer championships involve a large number of teams and are known to cause stress and loss of muscle mass besides other negative physical consequences. This study was designed to compare the effects produced by three types of protein supplements on body composition, biochemical parameters and performance of a top Brazilian professional soccer team during an actual tournament. Twenty-four athletes assessed as having a normal nutrient intake were divided into three groups according to supplementation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
13

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
1
20
0
13
Order By: Relevance
“…However, such studies did not evaluate the levels of NO. The present results showed that only WPH increased the NO content, which could be an alternative and/or concomitant mechanism of preserving glycogen, as well as a mechanism involved in the capacity of WPH to accelerate muscle recovery, reduce muscle damage (Lollo, Amaya-Farfan, & Carvalho-Silva, 2011) and prolong the permanence of the animal in the exercise. However, none of the tested peptides affected NO.…”
Section: Discussionmentioning
confidence: 54%
“…However, such studies did not evaluate the levels of NO. The present results showed that only WPH increased the NO content, which could be an alternative and/or concomitant mechanism of preserving glycogen, as well as a mechanism involved in the capacity of WPH to accelerate muscle recovery, reduce muscle damage (Lollo, Amaya-Farfan, & Carvalho-Silva, 2011) and prolong the permanence of the animal in the exercise. However, none of the tested peptides affected NO.…”
Section: Discussionmentioning
confidence: 54%
“…Morifuji et al (2009) showed that the peptide Ile-Leu, from among seven possible dipeptides containing branched-chain amino acids from the milk-whey proteins, was capable of increasing the uptake of glucose by isolated rat muscle. The reports suggest that far from being unsafe, these alterations are consistent with the observed physiological advantages, such as greater endurance exercise performance, better post-exhaustion glycemic levels, and preserved blood total protein and albumin levels (Morifuji et al, 2009;Faria et al, 2012;Lollo et al, 2011).…”
Section: Introductionmentioning
confidence: 66%
“…Moreover, it has been observed that a whey protein hydrolyzate is capable of reducing the levels of creatine kinase in both exercising rats (Abecia-Soria, 2010) and soccer players (Lollo et al, 2011), which was originally understood to be the result of the antioxidant capacity of some bioactive peptides present in the hydrolyzate (Peng, Siong and Kong, 2009;Ren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…fresh cow milk containing approximately 3.5% total protein, out of which 80 % casein, 15% whey protein, as well as vitamins, and lipids that provides necessary ingredients for growth [1,2]. In other words, energy (carbohydrate) obtained from milk in the form of lactose (sugar), nitrogen (protein; subcomponents of micro fractions) and rich source of calcium (for bones) [3,4]. Most of the biologically active components (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…lactoferrin, lactoperoxidase, lysozyme, and immunoglobulins etc.) that are present in the whey fraction of milk which showed antimicrobial properties [3,4]. Whey proteins mean that protein which is separated out from the casein and these are purified into different concentrations and are generally useful for wound healing, weight loss, infant health etc.…”
Section: Introductionmentioning
confidence: 99%